2016
DOI: 10.1002/ajp.22556
|View full text |Cite
|
Sign up to set email alerts
|

Socialization in pigtailed macaques (Macaca nemestrina)

Abstract: In response to new emphasis by regulatory agencies regarding socialization, behavioral management programs are allocating greater resources to maximize socialization opportunities for laboratory primates. Information regarding predictors of compatibility and risk of injury for all laboratory-housed species of macaques are needed to make social introductions and pairings as efficient and safe as possible. This study presents data on 674 pairs of pigtailed macaques (Macaca nemestrina) at the Washington National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Both the Animal Welfare Act and the Guide recommend that behavioral management plans should be tailored to each species [see also Williams et al, ; Worlein et al, ]. The Guide states that “group composition is critical and numerous species‐specific factors such as age, behavioral repertoire, sex, natural social organization, breeding requirements, and health status should be taken into consideration when forming a group” [NRC, , p. 59].…”
Section: Introductionmentioning
confidence: 99%
“…Both the Animal Welfare Act and the Guide recommend that behavioral management plans should be tailored to each species [see also Williams et al, ; Worlein et al, ]. The Guide states that “group composition is critical and numerous species‐specific factors such as age, behavioral repertoire, sex, natural social organization, breeding requirements, and health status should be taken into consideration when forming a group” [NRC, , p. 59].…”
Section: Introductionmentioning
confidence: 99%
“…Second, it is somewhat surprising that body weight differences did not contribute to the predictability of the statistical model, since it has been reported previously (Baker, ) at least among males (rhesus macaques (Capitanio, Blozis, Snarr, Steward, & McCowan, ); vervets ( Chlorocebus aethiops ) (Jorgensen et al, ). The role of weight may vary by species (e.g., pigtailed macaques ( Macaca nemestrina ); Worlein et al, ); cynomolgus macaques ( M. fascicularis Abney, Toscano, Poor, & Moomaw, ). Such analyses, however, may be very vulnerable to the inclusion of sexually‐immature animals in the subject pool (Maguire‐Herring, Stonemetz, Lynch, & Fahey, ; West et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For some of these studies, contrasting findings may relate to the fact that the focus is on introduction success per se, rather than injury. Indeed, Worlein et al () found differences in predictors between wounding and compatibility in pigtailed macaques. It is important for the reader to be aware that the findings of the current study relate only to the former and not the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest challenges associated with managing a socialization program for nonhuman primates in the laboratory is accurately assessing the cost–benefit ratio associated with formation of any new groups or pairs [Truelove et al, ]. Worlein et al [] correctly point out that these costs include pre‐screening animals for behavior characteristics by both behavioral and care staff, as well as time moving the animals, and dealing with the consequences of unsuccessful pairing attempts. This is especially true when socializing adult males of the species typically seen in laboratory research [Baer, ; Baker, ], and as reported here for owl monkeys.…”
Section: Discussionmentioning
confidence: 99%